1980
DOI: 10.1111/j.1432-1033.1980.tb04453.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of 2e- and le- Reduction Modes of the Flavin Chromophore as Studied by Flash Photolysis

Abstract: Evidence is given for the fact that the excited flavin triplet (3F10*x) exhibits competitive le-and 2e-transfer chemistry, depending on the nature of the photosubstrate. As an 'external' photoreductant, the 2e-donor borohydride has been investigated. Borohydride is found to compete effectively with the 'internal' 1 e-donors, namely excess starting flavin in the ground state (Flax) and, as primary product, (alky1)dihydroflavin (RFl,,dH). It will be shown that some of the flavin radicals, observed by earlier aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…The decay rate parameter of the radicals, ks, was determined [(4 2 0.7) x 10' M -k ' ] from the second order analysis of LFH. after the disappearance of 'LF, which is not different from the published values (6.2 x 10' M-ls-': Vaish and Tollin, 1971 and 3.9 x 10' M-'s-': Hemmerich et al, 1980). When X' is LFH' and LF?, Eq.…”
Section: Decay Of Triplet State and Decay-and-rise Of Redox Intermedicontrasting
confidence: 43%
See 1 more Smart Citation
“…The decay rate parameter of the radicals, ks, was determined [(4 2 0.7) x 10' M -k ' ] from the second order analysis of LFH. after the disappearance of 'LF, which is not different from the published values (6.2 x 10' M-ls-': Vaish and Tollin, 1971 and 3.9 x 10' M-'s-': Hemmerich et al, 1980). When X' is LFH' and LF?, Eq.…”
Section: Decay Of Triplet State and Decay-and-rise Of Redox Intermedicontrasting
confidence: 43%
“…Lumiflavin was synthesized according to Hemmerich et al (1956) and recrystallized from formic acid. 1.4-Benzoquinone was used after recrystallization from water.…”
Section: Methodsmentioning
confidence: 99%
“…A model for the specific binding of flavins (coenzyme) to a protein (apoprotein) can be achieved by anchoring the flavin with a long aliphatic chain to the membrane and thus the flavin exposes its four active positions [42,67,101,102,109]. It has been shown that flavins in the artificial systems can undergo both le-and 2e-redox reactions [40,41].…”
Section: In Vitro Studies and Artificial Photoreceptorsmentioning
confidence: 99%
“…(a) The addition of nucleophilic substrates to yield the hydroquinonic form of the dye in the primary process (transfer of 2e--equivalents) as recently demonstrated by flash photolysis with the hydride and cyanide anion in the flavin photochemistry (Traber et a!., 1980a;Hemmerich et al, 1980;Traber et al, 1980b) and supposed with oxalate in the 5deazaflavin photochemistry (Goldberg et al, 1980) and (b) the transfer of unpaired electrons to yield the dye semiquinone anion and the substrate radical cation (ie--transfer) which is a common mechanism in dye photochemistry.…”
Section: Introductionmentioning
confidence: 99%